Relation between reading of the writings of Ellen White and christian commitment in seventh-day adventist members - Celant, Stephenson (2020)
This study aims to determine the relationship between the reading of the writings of Ellen White and christian commitment in Adventist people in Ecuador. 120 seventh-day adventist church members participated and answered two instruments: the first related to the level of reading and understanding and the second related to christian commitment, which took into account the dimensions of “communion,” “relationship” and “mission.” The results of this investigation show a value of significance p = .030 <α = .05, which indicates that the relationship between the variables is significant; and the Spearman correlation coefficient =, 557, which indicates an average correlation between the variables; therefore it is concluded that the reading of Ellen White books is significantly related to the level of christian commitment.